Lifestyles and metabolic syndrome in the adult and elderly population from Trujillo, Peru, 2019 - Carranza Paredes, Jordano Jackestuard (2021)
Objective.To determine the relationship of lifestyles and metabolic syndrome in the adult and elderly population in the city of Trujillo (Peru), between July and August 2019. Methods. The study was nonexperimental, descriptive, correlational and cross-sectional. The sample consisted of 227 adults and 44 elderlies. Metabolic syndrome was determined by criteria of harmonised ATP-III. To evaluate lifestyles, a questionnaire about snacks, fruits, vegetables, tobacco consumption, alcohol and physical activity was used. The statistical analysis used to relate both variables was the chi-square test. Results. It was found that 55% of adults and 73% of elderlies had metabolic syndrome. 18.9% of adults consumed snacks and had metabolic syndrome; while those who did not consume snacks and did not have metabolic syndrome represented23.3% (p = 0.037). 27.3% did not consume vegetables, they had metabolic syndrome; while 28.6% consumed vegetables, they did not have metabolic syndrome (0.044). Conclusion. Only the consumption of snacks and the consumption of vegetables were related to metabolic syndrome in adults